Political power, local policy uncertainty and IPO pricing - Colak, Gonul; Gounopoulos, Dimitrios; Loukopoulos, Panagiotis; Loukopoulos, Georgios (Journal of Corporate Finance, 2021)
Greater partisan alignment among lawmakers enhances their ability to respond rapidly to adverse shocks, but it also undermines the quality of checks and balances and encourages excessive governmental intervention in local areas aligned with the ruling party. We investigate how this form of local policy risk affects IPO underpricing. One standard-deviation increase in political alignment between local politicians and the federal government translates into an extra $1.58 million being left on the table, which corresponds to 5.39% of the average valuation discount. This effect is concentrated in firms that are vulnerable to legislative interventions and has important long-term implications. Our robustness analysis also shows that our baseline results are not sensitive to the inclusion/exclusion of influential states and years with high IPO activity.